Ferulic acid combined with aspirin demonstrates chemopreventive potential towards pancreatic cancer when delivered using chitosan-coated solid-lipid nanoparticles - Thakkar, Arvind (Cell Biosci, 2015)
BACKGROUND: The overall goal of this study was to demonstrate potential chemopreventive effects of ferulic acid (FA), an antioxidant, combined with aspirin (ASP), a commonly used anti-inflammatory drug for pancreatic cancer chemoprevention, using a novel chitosan-coated solid lipid nanoparticles (c-SLN) drug delivery system encapsulating FA and ASP. RESULTS: Our formulation optimization results showed that c-SLNs of FA and ASP exhibited appropriate initial particle sizes in range of 183 ± 46 and 229 ± 67 nm, encapsulation efficiency of 80 and 78 %, and zeta potential of 39.1 and 50.3 mV, respectively. In vitro studies were conducted to measure growth inhibition and degree of apoptotic cell death induced by either FA or ASP alone or in combination. Cell viability studies demonstrated combinations of low doses of free FA (200 µM) and ASP (1 mM) significantly reduced cell viability by 45 and 60 % in human pancreatic cancer cells MIA PaCa-2 and Panc-1, respectively. However, when encapsulated within c-SLNs, a 5- and 40-fold decreases in dose of FA (40 µM) and ASP (25 µM) was observed which was significant. Furthermore, increased apoptosis of 35 and 31 % was observed in MIA PaCa-2 and Panc-1 cells, respectively. In vivo studies using oral administration of combinations of 75 and 25 mg/kg of FA and ASP c-SLNs to MIA PaCa-2 pancreatic tumor xenograft mice model suppressed the growth of the tumor by 45 % compared to control, although this was not statistically significant. In addition, the immunohistochemical analysis of tumor tissue showed significant decrease in expression of proliferation proteins PCNA and MKI67, and also increased expression of apoptotic proteins p-RB, p21, and p-ERK1/2 indicating the pro-apoptotic role of the regimen. CONCLUSION: Combination of FA and ASP delivered via a novel nanotechnology-based c-SLN formulation demonstrates potential for pancreatic cancer chemoprevention and could be a promising area for future studies.